Orthopedics of the Upper and Lower Limb - Iyer, K. Mohan (Springer London : Imprint: Springer, 2013)
Orthopedics of the Upper and Lower Limb has been written to serve as a general introduction to the field of orthopedics and trauma for the regions of the upper and lower limb. It is composed of a number of commonly seen disorders and with a corresponding therapeutic pathway, clearly explained with numerous x-rays and diagrams to aid the reader in their understanding of these useful procedures. The book is intended as a basic resource for trainees and junior surgeons, but will also be useful to more experienced specialists who require an easy to follow clinical guide to assist in day to day practice of orthopedic and trauma disorders of the upper and lower limb.